2022
DOI: 10.1093/ptj/pzac153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Programs on Functional Capacity and Quality of Life in People With Acquired Brain Injury: A Systematic Review and Meta-Analysis

Abstract: Objective The aims of this systematic review and meta-analyses were to evaluate the effects of exercise on the functional capacity and quality of life (QoL) of people with acquired brain injury (ABI) and to analyze the influence of training variables. Methods Five electronic databases (MEDLINE, Cochrane Library, CINAHL, SportDiscus, and Web of Science) were searched until October 2021 for clinical trials or experimental studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…As highlighted in earlier research, the proposed sport-based design emphasizes the importance of notably addressing the social domain within ABI rehabilitation, as the focus on the physical domain still predominates in this context. Further studies that integrate sport-based elements into their therapeutic approaches are needed to achieve higher levels of social inclusion within the functional rehabilitation field [9,21,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As highlighted in earlier research, the proposed sport-based design emphasizes the importance of notably addressing the social domain within ABI rehabilitation, as the focus on the physical domain still predominates in this context. Further studies that integrate sport-based elements into their therapeutic approaches are needed to achieve higher levels of social inclusion within the functional rehabilitation field [9,21,41].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have highlighted the positive outcomes of exercise therapy programs for people with ABI. Based on motor learning principles, several systematic reviews have consistently demonstrated the activation of supplementary motor areas and more consistent functional recovery compared to usual care alone [8][9][10][11][12]. In terms of design, multidisciplinary approaches that emphasize the integration of exercise therapy with social leisure activities are considered essential to elicit neuroplastic adaptations that enhance physical recovery [11,[13][14][15], and address cognitive and behavioral sequelae following ABI [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, balance disorders are strongly associated with a high rate of falls, which places a significant burden on patients with stroke and their families (7,8). Several studies have shown that exercise training positively affects balance improvement (9)(10)(11) and that balance and gait training (BGT) is considered an essential aspect of fall prevention (12)(13)(14). Therefore, involving BGT in the balance rehabilitation program for patients with stroke has become particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…However, among other neurological populations, positive long-term exercise behavior change has been demonstrated. This includes those with Parkinson’s disease [ 17 , 18 , 19 , 20 ], the traumatic brain injury population [ 21 ], post-stroke populations [ 22 , 23 ], and those living with spinal cord injury [ 24 ]. Furthermore, positive exercise behavior change, and health benefits have been demonstrated with these long-term programs in community-based [ 17 , 18 , 20 , 22 , 25 ] and group settings [ 17 , 18 , 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%